Hydrocele of the Canal of Nuck with Endometriosis: Right-Side Dominance Confirmed by Literature Review and Statistical Analysis. (5th May 2020) - Nagase, Shunsuke; Ogura, Kanako; Ashizawa, Karin; Sakaguchi, Asumi; Wada, Ryo; Matsumoto, Toshiharu
Abstract : Introduction . The canal of Nuck is an embryological remnant of the peritoneal pouch that extends into the labium majus of women. Hydrocele is the most common presentation, but only a small number of cases are reported in association with endometriosis. Case Presentation . The patient is a 45-year-old woman who presented with left inguinal mass with persistent pain. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed a 30 mm cystic mass, and a hydrocele of the canal of Nuck (HCN) was suspected. The excised mass was a cyst containing yellow-tan serous fluid, and the cyst wall was lined by mesothelium. The morphology was consistent with conventional HCN. However, since several foci of endometrial-like epithelium and stroma were identified beneath the mesothelium, the mass was diagnosed with HCN with endometriosis (EM-HCN). Discussion . Right-side dominance of EM-HCN is suggested by several authors, but a thorough review has never been performed. For the first time, we reviewed the literature and statistically confirmed that EM-HCNs dominantly occur on the right side compared to those without endometriosis. We consider that this supports the theory that endometriosis derives from retrograde menstruation of endometrial tissue through fallopian tubes. When endometriosis is discovered in HCN, the clinician should be aware of the possibility of pelvic endometriosis.